New insights on cytotoxic activity of group 3 and lanthanide compounds: complexes with [N, N, N]‐scorpionate ligands. (30th July 2013) - Saturnino, Carmela; Bortoluzzi, Marco; Napoli, Mariagrazia; Popolo, Ada; Pinto, Aldo; Longo, Pasquale; Paolucci, Gino
Abstract Objectives In this work was to evaluate the cytotoxic activity of a series of monomeric group 3 and lanthanide (N, N, N)‐heteroscorpionate‐triflate complexes (M (OTf) 2 (cybpamd) (THF)) (Ln = Sc (2), Y (3), La (4), Nd (5), Sm (6), Dy (7), Yb (8); OTf = SO3CF3; cybpamd = N, N′‐dicyclohexyl‐2, 2‐bis‐(3, 5‐dimethyl‐pyrazol‐1‐yl)‐acetamidinate) having octahedral geometry around the metal atoms on the human epithelial lung adenocarcinoma (A549), human melanoma (A375), human cervical epithelial adenocarcinoma, human embryonic kidney (HEK‐293) and murine macrophages (J774.A1) cell lines. Methods All the tested compounds were incubated with cells for 72 h and their growth inhibition assessed by using MTT assay. Key findings On the cell line HEK‐293 complexes 5 and 7 show a reasonable activities, while the murine macrophage cell line (J774.A1), only the scandium 2 complex is not very active. All complexes tested are poorly active on human health adenocarcinoma lung epithelial (A549) and human melanoma (A375). Conclusions The group 3 and lanthanide (N, N, N)‐heteroscorpionate triflate‐complexes (M(OTf)2(cybpamd)(THF)) on murine macrophage (J774.A1) cell line, except that of scandium, show a reasonable activity. On human epithelial cervix adenocarcinoma (HeLa) complexes 3, 5 and 6 are significantly more active than cis‐platinum, as well as complex 5 is more active on human embryonic kidney (HEK‐293) cell line. All the tested complexes are poorly active on human epithelial lung adenocarcinoma (A549) and human melanoma (A375). The different behaviour of the complexes examined (2–8) let us hypothesize that the cytotoxic activity is related to the molecule as a whole and not only to the ligand or the metal ion separately.